Massive stellar systems: observational challenges and perspectives in the E-ELT era. Issue Volume 12:Issue S316(2015) (31st March 2017) - Bono, G.; Braga, V. F.; Ferraro, I.; Fiorentino, G.; Gilmozzi, R.; Iannicola, G.; Magurno, D.; Matsunaga, N.; Monelli, M.; Rastello, S.
Abstract: We introduce the empirical framework concerning optical and near-infrared (NIR) photometry of crowded stellar fields. In particular, we address the impact that linear detectors and analytical PSF played in improving the accuracy and the precision of multi-band color-magnitude diagrams (CMDs). We focus our attention on recent findings based on deep NIR images collected with Adaptive Optics (AO) systems at the 8-10m class telescopes and discuss pros and cons of the different approaches. We also discuss the estimate of the absolute age of globular clusters using a well defined knee along the lower main sequence. We mention the role which the current AO-assisted instruments will have in addressing longstanding astrophysical problems of the Galactic center. Finally, we outline the role of first generation of E-ELT instruments upon photometry and spectroscopy of crowded stellar fields.